STRENGTHENING THE MOTIVATION OF DRUGS ADDICTION IN AR-RAHMAN DRUGS REHABILITATION CENTER USING ISLAMIC PSYCHOTHERAPY APPROACH - Anggik; Edo Kurniawan; Fia Marsella Auliyah; Kemas Syarif hidayatullah; Regina Fatimah Azzahra; Ria Sukmala Dewi; Syafrizal Latif; Vivi Ananda Lorentia; Ricky Hindra Siregar; Nabilah Mufidah; Syahira Nurfadhilah Fadhli; Fedrik Kristoforus; Anindya Putri Rahma; Sukma Utama; Lusi Sesriani (CV. Doki Course and Training, 2023)
A drug addict is someone who is mentally ill, sick or a patient who needs treatment or assistance with rehabilitation, not punishment. The purpose of this study was to determine the effect of Islamic psychotherapy with the RUH motivational theory approach using the Cognitive Therapy Technique with the Socratic Questioning Technique for drug addicts. This research is a qualitative research with a phenomenal research model. The subjects of this study amounted to 4 people. Data obtained from interviews. Data analysis techniques were obtained from in-depth interviews, in this study the data were processed using interpretive phenomenological analysis (IPA). The data analysis process in the natural sciences approach aims to explore the importance of the subject's meaning in his personal and social life. The analysis carried out in this study is to describe one one by one the data were obtained from the results of in-depth interviews. The results showed that former drug addicts had unique experiences as a result of using drugs, both in negative and positive contexts.